Women’s Empowerment for Enhancing Family Economic Welfare from the Perspective of Maqashid Sharia - Lestari Ningrum, Anggun Fambudi; Asnawi, Nur; Khusnudin, Khusnudin (State of Islamic Institute Langsa, 2025)
Ideally, women’s empowerment is expected to enhance family economic welfare while simultaneously strengthening children’s education, asset management, and social responsibility in accordance with the principles of Maqashid Sharia. However, empirical realities indicate limitations in economic literacy, access to capital, and adequate social support, which hinder the optimal contribution of women to the family economy. This study aims to analyze the role of women’s empowerment in improving family economic conditions from the perspective of Maqashid Sharia and to examine its implications for the social and moral well-being of families. The research employs a qualitative field approach using a case study of the Al-Hikmah Women’s Cooperative in Drajat Village, Baureno District, Bojonegoro Regency. Primary data were collected through in-depth interviews with cooperative members, participatory observation, and documentation of economic activities, while secondary data were obtained from fiqh literature, scholarly journals, and documents related to Maqashid Sharia. Data analysis was conducted using descriptive qualitative methods, supported by source and technique triangulation to ensure the validity of the findings. The results indicate that women’s empowerment through cooperatives contributes to increased family income, strengthened asset management, support for children’s education, and the reinforcement of families’ social and moral values. The integration of Maqashid Sharia principles ensures that women’s economic empowerment generates not only material benefits but also spiritual and social impacts on community welfare.